Explicit expressions of the matrices H, L and S for the bending of symmetrically laminated anisotropic plates - Wang, Xu (2016)
Derived in this work are the explicit expressions of the three real matrices H, L and S in the Stroh-type formalism for the bending deformation of an anisotropic, linearly elastic plate based on the Kirchhoff theory. The plate is homogeneous in the thickness direction or symmetrically laminated about its mid-plane, and thus, the stretching and bending deformations are decoupled. The three real matrices are the counterparts of the Barnett–Lothe tensors in the Stroh formalism for generalized plane strain elasticity. Identities relating H, L and S are developed. Several applications are presented to demonstrate the usefulness of the derived expressions of H, L and S.